Evaporação de água do solo na fase inicial de desenvolvimento das culturas do milho e soja - Saldanha, Gisele Schirmann (2009)
The principal element for plants is water, which is an important mainly production in a non-irrigated areas, and even more in places which haves insufficient rainfall. The use of straw protects soil from evaporation keeping the soil moisture. This study was made to quantify the water loss from the soil in the initial stages of maize and soybean cultures in the no-till farming system. The research was developed in an experimental area that belongs to the Departamento de Engenharia Rural of Universidade Federal de Santa Maria. The study was divided in two experiments, one that was done with maize was conducted starting in December, 16th 2007 and finishing in January, 16th 2008; the other experiment, done with soybean, was proceeded between January 17th and March 1st, 2008; both experiments were conducted under a mobile straw cover, which was used when it rained. The experiments occurred whit five different treatments, no-tillage farming system without cover, no-tillage farming system with 3.0 Mg ha-¹ of bristle oat straw (Avena strigosa Screb); no-tillage farming system with 6.0 Mg ha-¹ of bristle oat straw (Avena strigosa Screb); no-tillage farming system with 3.0 Mg ha-¹ of oat and tare (Vicia Sativa L.) straw. The blend it was composed of 75% of oat and 25% of tare. The water loss was determined in two drying soil cycles in the maize culture, and three cycles for the soybean culture, then making an water accountancy of soil portions, the first portion was from 0 to 20 cm, and the second portion was from 20 to 40 cm, based on the volume of humidity data, determined with TDR measurement in intervals from 15 minutes. It was compared the first drying cycle the both experiments following the Kc Dual methodology of cultivation, to the results obtained, the presence of 6 Mg ha-1of oat straw in the surface shrink down 26.3% the maximum values of evaporation estimated to the maize culture. In the soybean cultivation there was a reduction of 52%, when there was a cover of 6 Mg ha-1 of oat straw.